2009
DOI: 10.1021/ef8010993
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Minerals in Lignites and Intraseam Sediments from the Achlada Basin, Northern Greece

Abstract: Seven core samples (five lignite samples and two intraseam nonlignite rock samples) from the Achlada open-cut mine in northern Greece were characterized by X-ray diffraction (XRD) and X-ray fluorescence (XRF) techniques. Quantitative evaluation of the mineral phases in each sample was made from the powder X-ray diffractograms using Siroquant commercial interpretation software, which is based on Rietveld principles. The main minerals in the low-temperature ash (LTA) ash of the lignites are kaolinite and illite,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
0
5
0
3
Order By: Relevance
“…For example, the lowest percentage of SO 3 in Table III occurs in sample 2, which also has the lowest percentage of CaO, and the highest SO 3 percentage occurs in sample 6, which has the highest CaO percentage. Links between CaO and SO 3 in ashes prepared under similar conditions are discussed further by Koukouzas et al (2009).…”
mentioning
confidence: 94%
“…For example, the lowest percentage of SO 3 in Table III occurs in sample 2, which also has the lowest percentage of CaO, and the highest SO 3 percentage occurs in sample 6, which has the highest CaO percentage. Links between CaO and SO 3 in ashes prepared under similar conditions are discussed further by Koukouzas et al (2009).…”
mentioning
confidence: 94%
“…However, the areas where Fe-rich chlorite in the coal levels are seen as pore fillings, may also be genetically linked to diagenetic origin (Bartier et al, 1998). Kaolinite, on the other hand, may have formed by the in situ / authigenic deposition of silicon and aluminum elements dominant in these environments as a result of the chemical decomposition of feldspars (mostly sodic plagioclases) in high water-active environments (Koukouzas et al, 2009) and also can be transported detritically to this environment (Keller, 1978). Non-clay minerals such as quartz, feldspar, cristobalite, opal-CT, amphibole, and zeolite (natrolite) were detected in the middle-late Miocene pyroclastic deposits.…”
Section: Discussionmentioning
confidence: 99%
“…The EDX analysis of these plates shows similarities to kaolinite (Table 4). The concentration of kaolinite, especially in the coalbearing levels, can be attributed to the autogenetic deposition of silicon and aluminum there (Koukouzas et al, 2009).…”
Section: Scanning Electron Microscope (Sem-edx) Determinationsmentioning
confidence: 99%
“…Pollen analysis and a microfaunal study (Ioakim, 1984;van de Weerd, 1979) have concluded in an early Ruscinian age (lower boundary: 5.3 Ma) for the lower members of the unit and a late Ruscinian one for the upper members (Koufos, 1982). Current studies (Koukouzas et al, 2009(Koukouzas et al, , 2010 have shown that the Achlada deposits belong to the Komnina lignite sequence, which is correlated to chron C3An.1n (6.01-6.28 Ma) (Weber et al, 2012). (iii) The upper unit (Lofi formation) presents alternations of clays, marls, marly breccias, and sandy conglomerates.…”
Section: Introductionmentioning
confidence: 87%